Pengaruh Pengaruh Literasi Digital terhadap Praktik Green Marketing melalui Inovasi Pemasaran pada UMKM Kuliner di Tenggarong - Adji Dara Apta Pranata; Akbar , Ali; Eka Ningsih, Kartina (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of digital literacy on green marketing practices through marketing innovation among culinary MSMEs in Tenggarong. Using a quantitative approach, data were collected from 169 MSME owners through questionnaires and analyzed using SEM-PLS (SmartPLS 4.1.1.6). The results indicate that digital literacy significantly influences marketing innovation, and marketing innovation significantly affects green marketing. However, digital literacy does not directly affect green marketing. Marketing innovation mediates the relationship between digital literacy and green marketing. These findings imply that strengthening digital literacy should be integrated with marketing innovation strategies to effectively promote sustainable marketing practices among MSMEs. Keywords: Digital Literacy; Marketing Innovation; Green Marketing; MSMEs; Sustainable Marketing; Digital Transformation; Culinary SMEs; Mediation Effect